2021
DOI: 10.1007/s11764-021-01028-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic systolic dysfunction on contemporary echocardiography in anthracycline-treated long-term childhood cancer survivors: a systematic review

Abstract: Purpose Echocardiographic surveillance for asymptomatic left ventricular systolic dysfunction (ALVSD) is advised in childhood cancer survivors (CCS), because of their risk of heart failure after anthracycline treatment. ALVSD can be assessed with different echocardiographic parameters. We systematically reviewed the prevalence and risk factors of late ALVSD, as defined by contemporary and more traditional echocardiographic parameters. Methods We searched d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
(100 reference statements)
2
18
0
Order By: Relevance
“…A recent systematic review showed that the use of longitudinal strain identifies a higher prevalence of asymptomatic left ventricular systolic dysfunction in anthracycline-treated CCS compared to the use of LVEF [ 13 ]. However, its prognostic implications in CCS remain unknown [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review showed that the use of longitudinal strain identifies a higher prevalence of asymptomatic left ventricular systolic dysfunction in anthracycline-treated CCS compared to the use of LVEF [ 13 ]. However, its prognostic implications in CCS remain unknown [ 5 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of pre-and during-treatment imaging suitable for GLS analysis could contribute to there still being little evidence linking reduced GLS to adverse outcomes in this population. However, given the large cumulative incidence of heart failure in CCS with a long latency time after cardiotoxic treatment [6], the mounting evidence that GLS is impaired in CCS, and that GLS precedes cardiotoxicity in adult cancer survivors, it is probably useful to include GLS in the long-term follow-up [34]. Further studies in this regard are warranted.…”
Section: Resting Cardiac Functionmentioning
confidence: 99%
“…Recently, the American Society of Echocardiography and European societies recommended the Global Longitudinal Strain (GLS), from speckle tracking echocardiography (STE), as a marker of myocardial dysfunction 8–11 . Indeed, it may be associated with an early sign of evolving cardiomyopathy among childhood cancer survivors treated with anthracyclines despite their normal LVEF 12–15 . However, GLS represents only one component of LV strains.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Indeed, it may be associated with an early sign of evolving cardiomyopathy among childhood cancer survivors treated with anthracyclines despite their normal LVEF. [12][13][14][15] However, GLS represents only one component of LV strains. A comprehensive approach to assess LV systolic function needs to combine GLS with circumferential strains, 16 and also LV twisting mechanics.…”
Section: Introductionmentioning
confidence: 99%